(untitled) (Discourse of Law and Administration, 2023)
The publication concerns the reconstruction of the notary’s duties in the field of notarial activities in the event of death. It indicates the formal duties of a notary, taking into account their impact on the validity of the declaration of will. The second layer is the broadly understood defects of the declaration of will in both psychiatric and psychological terms. In this context, publications in the field of medical sciences as well as forensic psychiatric opinions were cited. An in-depth analysis of court decisions, in particular the Supreme Court, in the scope of the presented issues was also made.